If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 3) + -1(x + -2) = 0 Reorder the terms: 4(3 + 2x) + -1(x + -2) = 0 (3 * 4 + 2x * 4) + -1(x + -2) = 0 (12 + 8x) + -1(x + -2) = 0 Reorder the terms: 12 + 8x + -1(-2 + x) = 0 12 + 8x + (-2 * -1 + x * -1) = 0 12 + 8x + (2 + -1x) = 0 Reorder the terms: 12 + 2 + 8x + -1x = 0 Combine like terms: 12 + 2 = 14 14 + 8x + -1x = 0 Combine like terms: 8x + -1x = 7x 14 + 7x = 0 Solving 14 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 7x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 7x = 0 + -14 7x = 0 + -14 Combine like terms: 0 + -14 = -14 7x = -14 Divide each side by '7'. x = -2 Simplifying x = -2
| 2y/3-y/4=15 | | 2x^2+16x+32=17 | | 90x^2+84x^9+105= | | 7(2x+3)=4(x-5)-17 | | -v+12= | | X^4-18x^2+18=o | | -x^2-2x+1=9 | | x+3+7x-9=82 | | 5(y+-7)+-2y=1+-3[(4y+7)+-2(y+-3)] | | 10r-r= | | 5x^2+26x+32=0 | | 3(4x-2y)+2(x+2y)= | | 2x+11=6x-5-4x | | 11x-3=2x+9 | | 4x/3+2=5 | | -35x+12=28x+19 | | 2x^2+3((-2x+13)/3)^2-35=0 | | A+B+B+B+80+9=100 | | 4=ln(y+4) | | 4x+28x-32=0 | | 4(x-6)-6=x-14 | | 6*3/7*3*1/3/1*2/7 | | 4=Ln(y+1) | | 11/5n=4n+20 | | 6x+8=6x-13 | | -13.00+2.00x= | | ProveA+B+B+B+80+90=100 | | 0.1x+(3x+20)/5=0.5 | | (3x-2y+1)dx+(3x-2y+3)dy=0 | | 4(x-6)-6=4x-14 | | y(4x+y)dx-2(x^2-y)dy=0 | | 3(x+6)-4=6x-2 |